2014
DOI: 10.1080/1059924x.2014.886319
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Health Hazard Observations in Hmong Farming Operations

Abstract: Agricultural workers have a high risk of occupational injuries, illnesses, and fatalities. However, there are very few standardized tools available to assess safety and health in agricultural operations. Additionally, there are a number of groups of agricultural workers, including Hmong refugees and immigrants, for which virtually no information on safety and health conditions is available. This study developed an observation-based methodology for systematically evaluating occupational health and safety hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…Of note, as a complement to these participatory approaches, traditional worksite walk-through inspections were conducted on participants’ farms. Findings from these walkthroughs are reported elsewhere (Neitzel, Krenz, & de Castro, in press). Collectively, these various assessment methods offered a unique approach that triangulated data sources to gain a rich, multidimensional perspective of agricultural safety and health issues among Hmong refugee farmers, which may guide the development of possible intervention projects in the future.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of note, as a complement to these participatory approaches, traditional worksite walk-through inspections were conducted on participants’ farms. Findings from these walkthroughs are reported elsewhere (Neitzel, Krenz, & de Castro, in press). Collectively, these various assessment methods offered a unique approach that triangulated data sources to gain a rich, multidimensional perspective of agricultural safety and health issues among Hmong refugee farmers, which may guide the development of possible intervention projects in the future.…”
Section: Discussionmentioning
confidence: 98%
“…The project’s community liaison, who is of Hmong descent, was present at both workshops to assist with language translation. Between these two sessions, during the actual growing season, participants engaged in photovoice and walk-through observations of participants’ farms using industrial hygiene approaches (Neitzel, Krenz, & de Castro, in press). …”
Section: Methodsmentioning
confidence: 99%
“…Evidences of the associations between gastric disorders and pesticide application by rural workers have been reported in the literature. (2)(3)(4)(5)(6) A study involving individuals who applied pesticides reported gastrointestinal symptoms, including nausea, vomiting, severe abdominal pain, and retrosternal pain or discomfort. These symptoms were attributed to gastrointestinal irritation produced by the release of phosphine into the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…(10,11) Similarly, the evaluation of the rural population is very important to identify gastric disorders and infections because of this group's socioeconomic status (7) and the type of work they perform, which is tiring, exhausting, heavy, without a fixed schedule, and its success is dependent not only on workers but also on the weather. (6) Rural workers also perform domestic work, which can exacerbate physical, mental, and temporal demands in the execution of multiple activities. A previous study involving men and women and investigating on the use of their time to reconcile work and family life indicated that women were tied to domestic responsibilities and that this might contribute to increased stress.…”
Section: Introductionmentioning
confidence: 99%
“…1 Agricultural workrelated injury can be defined as an acute injury that occurs while doing farm work or travelling to or from work. Agricultural upper limb injuries are important causes of mortality and morbidity for all age groups.…”
Section: Introductionmentioning
confidence: 99%